Continuous Quality Improvement and Comprehensive Primary Health Care: A Systems Framework to Improve Service Quality and Health Outcomes - McCalman, Janya; Bailie, Ross; Bainbridge, Roxanne; McPhail-Bell, Karen; Percival, Nikki; Askew, Deborah; Fagan, Ruth; Tsey, Komla (Frontiers in Public Health, 2018)
Continuous quality improvement (CQI) processes for improving clinical care and health outcomes have been implemented by primary health-care services, with resultant health-care impacts. But only 10–20% of gain in health outcomes is contributed by health-care services; a much larger share is determined by social and cultural factors. This perspective paper argues that health care and health outcomes can be enhanced through applying CQI as a systems approach to comprehensive primary health care. Referring to the Aboriginal and Torres Strait Islander Australian context as an example, the authors provide a systems framework that includes strategies and conditions to facilitate evidence-based and local decision making by primary health-care services. The framework describes the integration of CQI vertically to improve linkages with governments and community members and horizontally with other sectors to influence the social and cultural determinants of health. Further, government and primary health-care service investment is required to support and extend integration and evaluation of CQI efforts vertically and horizontally.